A systematical review of 3D printable cementitious materials. (20th May 2019) - Lu, Bing; Weng, Yiwei; Li, Mingyang; Qian, Ye; Leong, Kah Fai; Tan, Ming Jen; Qian, Shunzhi
Highlights: A systematical review of 3D printable cementitious materials was conducted. A multi-level material design (MMD) for development of 3DPCM was proposed. MMD is illustrated via inter-connected pyramids, i.e. material, printing & structure. Based on MMD, three different levels of material design are reviewed successively. Abstract: 3D printing, or additive manufacturing, is a technology which adopts layer-by-layer additive deposition process to build three-dimensional objects. Over the past decade, 3D printing has been attracting more and more attention in the building and construction industry. Compared with conventional concrete casting techniques, 3D printing contributes to higher efficiency with freeform construction, greatly reduced labor and much less construction waste. However, 3D printable cementitious materials are different from conventional concrete in terms of rheology, printability, and mechanical performances. This paper aims to systematically bridge the gap between the requirement and research and development of 3D printable cementitious materials to date. Guided by 3D printing process and multi-level design of cementitious materials, the requirements for 3D printable cementitious material at different material development levels are discussed. This paper provides insights for the future development of 3D printable cementitious materials for building and construction by controlling the basic inputs of materials to obtain desired structural performance.